PERAN MAJELIS PELAYANAN SOSIAL (MPS) MUHAMMADIYAH UNTUK MENINGKATKAN KUALITAS PENGASUHAN ORANG TUA DALAM PELATIHAN GOOD PARENTING MELALUI MEDIA SOSIAL WHATS APP - Siti Nuraeni (Comm-Edu (Community Education Journal), 2020)
ABSTRACT This research is motivated by the lack of competency in parenting care for MPS Muhammadiyah's children. The purpose of this study is: to reveal data about good parenting planning, the process of implementing good parenting, the results of implementing good parenting. The cornerstone of the theory in this study, researchers refer to several concepts, namely: understanding parenting and understanding good parentin. The approach used in this research is a qualitative approach using a case study method. Data collection techniques used are observation, interviews, documentation studies. This research is divided into three stages, namely long-term, medium-term and short-term planning, the implementation of which involves the caregivers of children in good parenting education and training programs while the results of this study are increased parental competence in parenting. The conclusion of this study is that good parenting education and training can increase the competence of parents in caring for their children so they can instill the love of parents for their children. Keywords: Parenting, Good Parenting, MPS Muhammadiyah